Evaluation of Groundwater Quality in Deeg Tehsil of Bharatpur District, Rajasthan: Assessment of Groundwater Quality in Deeg Tehsil, Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Water is one of the basic human needs and directly related to human health. Thus safe, wholesome and adequate drinking water for every human is constitutional right. Ground water is the major source of drinking water for the residents of Deeg tehsil since the surface water is very limited. Ground water abstraction is increasing day by day due to its increasing demand for various uses. In the present study, the evaluation of ground water quality in this region is taken up. 133 water samples have been collected during April 2015-Sept.2015. Alkalinity, Hardness, Fluoride, Nitrate, Total Dissolved Solids, Chloride contents have been analysed from the collected water samples. Some of samples show the high concentration levels of TDS, Hardness, Chloride, Nitrate. This study reveals the present status of ground water quality. It is essential to assess the ground water resources for efficient ground water management.